Molecular Analysis of Iron Deficiency Response in Hexaploid Wheat - Wang, Meng; Kawakami, Yuta; Bhullar, Navreet K. (Frontiers in Sustainable Food Systems, 2019)
Iron deficiency leads to severe chlorosis in crop plants, including wheat, thereby reducing total yield and quality. Furthermore, grains of most bread wheat varieties are poor source of iron, which is vital for human nutrition. Despite the significance, iron uptake and translocation mechanisms in bread wheat have not been studied in detail, particularly under iron limited growth conditions. In this study, bread wheat plants were grown under iron deficiency stress until maturity. Data were collected at three distinct developmental time points during grain-filling. The plants experiencing low iron availability exhibited significantly lower chlorophyll content as well as low iron concentration in leaves and grains. The expression levels of bread wheat genes homologous to iron deficiency responsive genes of rice, barley, and Arabidopsis were significantly changed under iron deficiency stress. The wheat homologs of genes involved in phytosiderophore (PS) synthesis and transport were significantly up-regulated in the iron-deficient roots through all development stages, confirming an important role of deoxymugineic acid (DMA) in iron acquisition. The up-regulation of NICOTIANAMINE SYNTHASE (NAS) and DEOXYMUGINEIC ACID SYNTHASE (DMAS) in flag leaves and grains suggested the involvement of nicotianamine (NA) and DMA in iron chelation and translocation in wheat, particularly at the commencement of grain-filling. In line with this, the homolog of gene encoding TRANSPORTER OF MUGINEIC ACID (TOM) was up-regulated in the wheat roots under iron deficiency. Additionally, genes encoding long-distance iron transporter YELLOW STRIPE-LIKE (YSL), the vacuolar transporter NATURAL RESISTANCE ASSOCIATED MACROPHAGE PROTEIN (NRAMP), and the transcription factor BASIC HELIX-LOOP-HELIX (bHLH), were also up-regulated upon iron starvation. A tissue specific and growth stage specific gene expression differences in response to iron deficiency stress were observed, providing new insights into iron translocation, storage and regulation in bread wheat.